Properties, characteristics and application of grinded Malpighia emarginata seeds in the removal of toxic metals from water - Silva, Adrielli C.P. [UNESP]; Jorgetto, Alexandre O. [UNESP]; Wondracek, Marcos H.P.; Galera, Rodrigo M. [UNESP]; Schneider, José F.; Saeki, Margarida J. [UNESP]; Pedrosa, Valber A. [UNESP]; Zara, Luiz F.; Castro, Gustavo R. [UNESP] (Elsevier, 2018)
Cadmium and copper, which are found in aquatic ecosystems, may be considered toxic and potentially toxic metal species, respectively. These metals tend to accumulate in plants and fish, besides their potential to be transferred to other animals and cause several diseases. Malpighia emarginata grinded seeds were simply prepared and applied as adsorbent in order to remove and assist the safe trace quantification of such elements. Dry biomass was characterized through FTIR, 13C-NMR, SEM, surface area measurements and through elemental analysis. Important structures, which may be involved in metal coordination, such as carboxylic acid, thiazole and amine groups, were identified. Malpighia emarginata seeds had its pHPZC determined (6.0) and the influence of dynamic contact time (kinetic) and pH on adsorption of Cu(II) and Cd(II) was investigated. Adsorption equilibrium was reached in less than 30 min, and it had good correlation with the pseudo-second-order kinetic model in Cu(II) and Cd(II). The Ns values were calculated through the modified Langmuir equation (0.103 and 0.098 mmol g−1 for Cu(II) and Cd(II), respectively), which showed results similar to those published in other studies. The preconcentration system accomplished enrichment factor of approximately 40-fold in Cu(II) and Cd(II). Such result evidenced that Malpighia emarginata seeds can be a low-cost procedure adopted to remove metallic species from aqueous samples, as well as to assist analytical methodologies in determining Cu(II) and Cd(II) traces.
Keywords: Biosorption; Chemisorption; Contaminated water; Toxic metals